2021
DOI: 10.1155/2021/5006248
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Recognition of Communication Signal Modulation Based on the Multiple‐Parallel Complex Convolutional Neural Network

Abstract: This paper implements a deep learning-based modulation pattern recognition algorithm for communication signals using a convolutional neural network architecture as a modulation recognizer. In this paper, a multiple-parallel complex convolutional neural network architecture is proposed to meet the demand of complex baseband processing of all-digital communication signals. The architecture learns the structured features of the real and imaginary parts of the baseband signal through parallel branches and fuses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…combination of CNN and LSTM exhibits outstanding performance in the field of automatic modulation recognition [12]. Huang et al developed a parallel branch architecture for processing the real and imaginary parts of baseband signals and proposed a CNN and LSTM integrated CLP algorithm, which significantly improves the performance of radio signal modulation recognition [13]. Yin et al constructed a Convolutional Neural Network modulation recognition model (SCAM) based on attention mechanisms to process raw I/Q sequence signals, and showed that attention mechanisms can significantly enhance automatic modulation recognition accuracy under low SNR conditions [14].…”
Section: Introductionmentioning
confidence: 99%
“…combination of CNN and LSTM exhibits outstanding performance in the field of automatic modulation recognition [12]. Huang et al developed a parallel branch architecture for processing the real and imaginary parts of baseband signals and proposed a CNN and LSTM integrated CLP algorithm, which significantly improves the performance of radio signal modulation recognition [13]. Yin et al constructed a Convolutional Neural Network modulation recognition model (SCAM) based on attention mechanisms to process raw I/Q sequence signals, and showed that attention mechanisms can significantly enhance automatic modulation recognition accuracy under low SNR conditions [14].…”
Section: Introductionmentioning
confidence: 99%